2013
DOI: 10.1038/ismej.2013.58
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity in cultured and wild marine cyanomyoviruses reveals phosphorus stress as a strong selective agent

Abstract: Viruses that infect marine cyanobacteria-cyanophages-often carry genes with orthologs in their cyanobacterial hosts, and the frequency of these genes can vary with habitat. To explore habitatinfluenced genomic diversity more deeply, we used the genomes of 28 cultured cyanomyoviruses as references to identify phage genes in three ocean habitats. Only about 6-11% of genes were consistently observed in the wild, revealing high gene-content variability in these populations. Numerous shared phage/host genes differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 68 publications
1
79
0
Order By: Relevance
“…This finding hints at the relative selective pressures these two key nutrients exert. The idea that limitation of a given nutrient leads to the gain of genes for uptake and assimilation of that nutrient is supported by numerous studies (Coleman and Chisholm, 2010;Kelly et al, 2013;Thompson et al, 2013). Here, we extend that idea to the quantitative explanatory power of the nutrient's concentration for predicting KO relative abundance.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…This finding hints at the relative selective pressures these two key nutrients exert. The idea that limitation of a given nutrient leads to the gain of genes for uptake and assimilation of that nutrient is supported by numerous studies (Coleman and Chisholm, 2010;Kelly et al, 2013;Thompson et al, 2013). Here, we extend that idea to the quantitative explanatory power of the nutrient's concentration for predicting KO relative abundance.…”
Section: Resultsmentioning
confidence: 64%
“…Several studies have shown that genes for nutrient acquisition are enriched in waters limited for those nutrients, for example, phosphate acquisition in the low-phosphate Mediterranean and Sargasso Seas (Coleman and Chisholm, 2010;Kelly et al, 2013;Thompson et al, 2013). Across the gradients of the Red Sea, numerous KOs for nutrient transport and assimilation were differentially distributed between nutrient-poor (surface and non-GAIW) and nutrientrich (deep and GAIW) samples.…”
Section: Environmental Covariation Patterns Of Individual Kosmentioning
confidence: 99%
“…Recently, Maat et al (2014) have evaluated the outcome of P limitation on viral infection in picoeukaryote Micromonas pusilla, reporting a prolongation of the latent period from 6 to 12 h, and an 80% reduction in viral burst sizes compared to P-replete conditions. Phosphorus stress has been pointed out as a strong selective agent, with some phage having in their genome host-like phosphorus assimilation genes that are upregulated when the host is phosphorous starved, thus promoting P acquisition necessary for phage dispersion (Kelly et al, 2013). In a similar way, it has been reported the presence of host-like photosynthesis genes in phage along with the capacity to express them and actively contribute to primary production during the infection (Sullivan et al, 2006).…”
Section: Viruses and Phytoplankton Mortalitymentioning
confidence: 88%
“…Interestingly, the pho4 gene, found in six OlVs, also has been found in many other marine eukaryotes and viruses (56). Similarly, a gene that encodes PstS, a protein that is involved in phosphate metabolism, is found in many prokaryotes and cyanophages (57). Multiple independent pho4 gene transfer events (with retention) have been proposed to occur between marine viruses and their hosts.…”
Section: Discussionmentioning
confidence: 99%